EFFECT OF DIFFERENT LEVELS OF HYDROGEN - Karagoz, Yasin; Koten, Hasan (YILDIZ TECHNICAL UNIV, 2019)
Compelling emission regulations and diesel engines damage on environment have led researchers to work on alternative fuels such as LPG and hydrogen in recent years. Diesel engine costs are also increasing, especially on the increased costs of after-treatment equipment used in diesel engines. It is also known that diesel engines release NOx and smoke emissions, which are highly harmful to the environment and to the living health. The effect of the emissions of LPG + H-2 (0%, 15%, 30% and 45%) with different energy contents at full load and same torque (70 Nm) at constant engine speed of 1200 rpm is investigated on CO, THC, NOx and Smoke emissions. From the results obtained, there was a slight increase in brake thermal efficiency, CO and THC emissions. However, significant improvement in NOx and smoke emissions has been achieved. The results show that using LPG + H-2 in diesel engines, older technology and lower cost after-treatment equipment can be used, and that NOx and smoke emissions of diesel engines can be reduced significantly. Also, using small amount of hydrogen (20% of total gas mixture) and LPG, an important improvement can be achieved, and the harmful effects of diesel engines can be suppressed thanks to unique properties of hydrogen fuel. Compelling emission regulations and diesel engines damage on environment have led researchers to work on alternative fuels such as LPG and hydrogen in recent years. Diesel engine costs are also increasing, especially on the increased costs of after-treatment equipment used in diesel engines. It is also known that diesel engines release NOx and smoke emissions, which are highly harmful to the environment and to the living health. The effect of the emissions of LPG + H-2 (0%, 15%, 30% and 45%) with different energy contents at full load and same torque (70 Nm) at constant engine speed of 1200 rpm is investigated on CO, THC, NOx and Smoke emissions. From the results obtained, there was a slight increase in brake thermal efficiency, CO and THC emissions. However, significant improvement in NOx and smoke emissions has been achieved. The results show that using LPG + H-2 in diesel engines, older technology and lower cost after-treatment equipment can be used, and that NOx and smoke emissions of diesel engines can be reduced significantly. Also, using small amount of hydrogen (20% of total gas mixture) and LPG, an important improvement can be achieved, and the harmful effects of diesel engines can be suppressed thanks to unique properties of hydrogen fuel.
Keywords: Liquefied Petroleum Gas; LPG; LPG + H-2; Common-Rail; FUEL DIESEL-ENGINE; DUAL-FUEL; DIRECT-INJECTION; PERFORMANCE; COMBUSTION; EMISSIONS; PARAMETERS; SYSTEM; Thermodynamics